Efforts to improve the smooth process of tank cleaning to prevent delays in loading and unloading activities at MT. Holiday rentals in Enim - Mika Engelina Malau; Budhi Santoso (Meteor STIP Marunda, 2025)
One of the cargoes transported using sea transportation services is oil cargo. To meet the needs of transporting oil cargoes, an innovative ship was created that can transport types of oil cargo, namely tankers. Tankers are a type of ship that has been designed to be able to transport various types of oil, chemical liquids to liquids. Systematic and correct tank cleaning methods include planning and preparation, implementation and evaluation. There are still remnants of tank cleaning in the cargo tank and there are still dangerous toxic gases in the cargo tank that exceed the ideal for H2S 0.1% and for CO 0.1%. Then for the level of O2 gas in the tank to be less than 21% (the ideal O2 is 21%) causes the tank cleaning process on board the ship to take too long. Resulting in losses for the company because the company received a fine sanction by the charterer. The purpose of the research is to improve the smoothness and find solutions because of the long tank cleaning process. This research is a type of research with a qualitative descriptive method. Data collection was carried out by interviews